Directional anchoring catalyst as well as preparation method and application thereof

By introducing NiaFe2-aO3 into the Fe-based oxide catalyst and anchoring directionally on the (110) crystal plane of α-Fe2O3, a directional anchoring catalyst with excellent catalytic performance was prepared, which solved the problem of insufficient activity and selectivity of existing catalysts and achieved efficient degradation of motor vehicle soot particulate matter.

CN119746865APending Publication Date: 2025-04-04CHINA UNIV OF PETROLEUM (BEIJING)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510014839.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

There is still room for improvement in the activity and selectivity of existing Fe-based oxide catalysts in catalyzing soot particulate oxidation reaction.

Method used

A directional anchoring catalyst is used, which consists of α-Fe2O3 and NiaFe2-aO3, which is anchored on the (110) crystal surface of α-Fe2O3. By a specific preparation method, a contact reaction of metal salt solution, hydrothermal reaction and calcination treatment, a nanosheet-like catalyst with excellent catalytic properties is prepared.

Benefits of technology

The catalyst has excellent stability and catalytic activity, and is suitable for high-temperature catalytic reactions, especially in the field of elimination of smoke particulate matter in motor vehicles. It can effectively reduce the emission of smoke particulate matter and reduce the harm to the environment and the human body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746865A_ABST
    Figure CN119746865A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts for motor vehicle tail gas treatment, and discloses a directional anchoring catalyst as well as a preparation method and application thereof. The catalyst contains alpha-Fe2O3 and Ni Fe < 2-a > O < 3 >, wherein a is more than 0.3 and less than or equal to 0.8; the catalyst is a nanosheet with the average thickness of 100 to 150 nm, and Ni Fe < 2-a > O < 3 > in the catalyst is anchored on the (110) crystal face of the alpha-Fe2O3. The oriented anchoring catalyst provided by the invention has excellent stability and catalytic activity, and has a wide application prospect in the field of elimination of soot particulate matters of motor vehicles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts for treating motor vehicle exhaust, and in particular to a directional anchored catalyst and a preparation method and application thereof. Background Art

[0002] The soot particles in motor vehicle exhaust refer to micron-sized carbonaceous particles produced by the combustion of diesel and gasoline. They have high adsorption and light absorption capabilities. These particles may cause respiratory diseases after entering the human respiratory tract, and long-term exposure may also lead to serious health problems such as cardiovascular disease and cancer, causing serious impacts on the atmospheric environment and human health.

[0003] Traditional emission control methods include oil refining, internal combustion engine improvement and catalytic after-treatment technology; among them, catalytic after-treatment technology has attracted much attention due to its advantages such as high efficiency and low cost.

[0004] From an economic point of view, iron-based catalysts are cheaper than rare earth materials, and the introduction of heteroatoms on this substrate can precisely tune the O 2 and NO adsorption and activation properties, thereby improving the catalytic smoke removal performance.

[0005] As one of them, Fe-based oxide catalysts have abundant lattice defects and redox ability, and are expected to play an important role in the catalytic oxidation reaction of soot particles.

[0006] At present, the preparation technologies of Fe-based oxide catalysts include sol-gel method, co-precipitation method, vapor deposition method and other methods. Researchers are committed to optimizing the preparation process and improving the performance and stability of the catalyst.

[0007] Domestic and foreign research teams are actively studying Fe-based oxide catalysts. Some research teams have improved the specific surface area and lattice defect density of the catalyst by improving the preparation process, further improving the activity and stability of the catalyst. However, the activity and selectivity of Fe-based oxide catalysts still have a lot of room for improvement. Summary of the invention

[0008] The purpose of the present invention is to provide an Fe-based oxide anchored catalyst with good catalytic activity and selectivity.

[0009] In order to achieve the above-mentioned object, the first aspect of the present invention provides a directional anchoring catalyst, wherein the catalyst contains α-Fe 2 O 3 and Ni a Fe 2-a O 3 ; Among them, 0.3<a≤0.8;

[0010] The catalyst is a nanosheet with an average thickness of 100-150 nm, and the Ni in the catalyst a Fe 2-a O 3 Anchored in the α-Fe 2 O 3 on the (110) crystal plane.

[0011] A second aspect of the present invention provides a method for preparing a directional anchored catalyst, the method comprising:

[0012] (1) adding ammonia monohydrate dropwise to a metal salt solution to carry out a contact reaction to obtain an intermediate I;

[0013] (2) subjecting the intermediate I to a hydrothermal reaction to obtain a precursor;

[0014] (3) calcining the precursor in an air atmosphere to obtain a directional anchored catalyst;

[0015] The metal salt solution contains Fe in a molar ratio of 1.5-4:1. 3+ and Ni 2+ ;

[0016] Calculated on the basis of metal ions, the dropping rate of the ammonia monohydrate is 0.04-0.10 mL / s for every 1 mmol of the metal salt solution.

[0017] The third aspect of the present invention provides a directional anchoring catalyst prepared by the method described in the second aspect.

[0018] The fourth aspect of the present invention provides the use of the directional anchored catalyst described in the first aspect or the third aspect in the elimination reaction of soot particles in the exhaust gas of a motor vehicle.

[0019] The Ni in the directional anchoring catalyst provided by the present invention a Fe 2-a O 3 Directed anchoring in α-Fe 2 O 3 The (110) crystal plane gives the catalyst more active sites.

[0020] The directional anchored catalyst provided by the present invention has excellent stability and catalytic activity, and is suitable for catalytic reactions that require high-temperature treatment, especially in the field of eliminating carbon smoke particles in motor vehicles. It can effectively reduce the emission of carbon smoke particles and reduce the harm of carbon smoke to the environment and human body. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a SEM image of the directional anchored catalyst prepared in Example 1 of the present invention;

[0022] Figure 2 This is the XPS graph of the directional anchored catalyst prepared in Example 1 of the present invention;

[0023] Figure 3 1 is the XRD diagram of each catalyst prepared in Examples 1 to 3 of the present invention, Comparative Example 1 and Comparative Example 2;

[0024] Figure 4 This is the stability performance test result of the directional anchoring catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0025] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0026] As mentioned above, the first aspect of the present invention provides a directional anchoring catalyst, which contains α-Fe 2 O 3 and Ni a Fe 2-a O 3 ; Among them, 0.3<a≤0.8;

[0027] The catalyst is a nanosheet with an average thickness of 100-150 nm, and the Ni in the catalyst a Fe 2-a O 3 Anchored in the α-Fe 2 O 3 on the (110) crystal plane.

[0028] Preferably, the α-Fe in the catalyst 2 O 3 and Ni a Fe 2-a O 3 The molar ratio of the content is 1:0.1-0.3.

[0029] Preferably, 0.4≤a≤0.6. The inventors of the present invention have found that in this preferred case, the prepared directional anchored catalyst has more excellent catalytic performance.

[0030] As mentioned above, the second aspect of the present invention provides a method for preparing a directional anchored catalyst, the method comprising:

[0031] (1) adding ammonia monohydrate dropwise to a metal salt solution to carry out a contact reaction to obtain an intermediate I;

[0032] (2) subjecting the intermediate I to a hydrothermal reaction to obtain a precursor;

[0033] (3) calcining the precursor in an air atmosphere to obtain a directional anchored catalyst;

[0034] The metal salt solution contains Fe in a molar ratio of 1.5-4:1. 3+ and Ni 2+ ;

[0035] Calculated on the basis of metal ions, the dropping rate of the ammonia monohydrate is 0.04-0.10 mL / s for every 1 mmol of the metal salt solution.

[0036] Preferably, in step (1), the metal salt solution is prepared by the following steps:

[0037] Will Fe(NO 3 ) 3 9H 2 O.Ni(NO 3 ) 2 6H 2 O and water are stirred to obtain the metal salt solution.

[0038] The present invention has no special requirements for the stirring conditions, and only requires that Fe(NO 3 ) 3 9H 2 O.Ni(NO 3 ) 2 6H 2 O is completely dissolved. Exemplarily, stirring is performed at 700 rpm-800 rpm for 20-40 min.

[0039] The present invention has no particular requirements on the type of water, and those skilled in the art can select it according to the known technical means in the art. For example, the water can be deionized water.

[0040] Preferably, in step (1), the amount of ammonia monohydrate used is 0.3-0.4 mL per 1 mmoL of the metal salt solution.

[0041] Preferably, the metal salt solution contains Ni 2+ and Fe 3+ of nitrate solution.

[0042] Preferably, in step (2), the conditions of the hydrothermal reaction include: a temperature of 150-180° C. and a time of 10-14 h. The inventors of the present invention have found that under this preferred condition, the prepared directional anchored catalyst has a more excellent catalytic performance.

[0043] Preferably, the hydrothermal reaction is carried out in a Teflon-lined stainless steel autoclave.

[0044] Preferably, the method further comprises: in step (2), naturally cooling the product after the hydrothermal reaction to room temperature, collecting the precipitate by centrifugation and drying the precipitate to obtain the precursor.

[0045] The present invention has no particular requirements for the drying conditions, and those skilled in the art can select the conditions according to known means in the art. Exemplarily, the drying is carried out in a vacuum drying oven at a temperature of 40-60° C. for 6-10 hours.

[0046] According to a preferred specific embodiment, the method further comprises: in step (3), first grinding the precursor into powder, and then calcining the powdered precursor.

[0047] Preferably, the average particle size of the powdered precursor is 5-10 nm.

[0048] It should be noted that the average particle size in the present invention refers to the particle size corresponding to when the cumulative particle size distribution fraction in the powdered precursor sample reaches 50% when tested by a nanoparticle size analyzer.

[0049] Preferably, in step (3), the calcination treatment conditions include: temperature of 450-550° C. and time of 3-6 h.

[0050] According to another preferred embodiment, in step (3), the calcination treatment conditions include: heating to 450-550° C. at a heating rate of 0.5-1.5° C. / min.

[0051] It should be noted that the calcination time in the present invention does not include the time required for heating.

[0052] Unless otherwise specified, the room temperature in the present invention is 23±2°C.

[0053] As mentioned above, the third aspect of the present invention provides a directional anchoring catalyst prepared by the method described in the second aspect.

[0054] As mentioned above, the fourth aspect of the present invention provides the use of the directional anchored catalyst described in the first aspect or the third aspect in the elimination reaction of soot particles in the exhaust gas of a motor vehicle.

[0055] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the instruments, reagents, materials, etc. involved are all conventional instruments, reagents, materials, etc., which can be obtained through regular commercial channels. Among them, unless otherwise specified, the reagents used are all commercially available analytically pure products.

[0056] Example 1

[0057] This example is used to illustrate the preparation of a directional anchored catalyst according to the formula and process parameters in Table 1 and the following method. The preparation method of the catalyst includes:

[0058] (1) Put Fe(NO 3 ) 3 9H 2 O.Ni(NO 3 ) 2 6H 2 O and deionized water were stirred at 750 rpm for 30 min to obtain a metal salt solution;

[0059] Adding ammonia monohydrate dropwise (at a dropping rate of 0.08 mL / s) into the metal salt solution for contact reaction to obtain intermediate I;

[0060] (2) transferring the intermediate I to a Teflon-lined stainless steel autoclave for hydrothermal reaction, naturally cooling the product after the hydrothermal reaction to room temperature, collecting the precipitate by centrifugation and drying it in a vacuum drying oven to obtain a precursor;

[0061] The drying temperature was 50°C and the time was 8h;

[0062] (3) The precursor is ground into powder (with an average particle size of about 8 nm), and the powdered precursor is calcined in an air atmosphere to obtain a directional anchored catalyst, named J1.

[0063] Unless otherwise specified, Examples 2-3 are all carried out using methods similar to those of Example 1, except for the formula and process, as shown in Table 1.

[0064] Comparative Example 1

[0065] (1) 5 mmol of Fe(NO 3 ) 3 9H 2 O and deionized water were stirred at 750 rpm for 30 min to obtain a metal salt solution;

[0066] Adding ammonia monohydrate dropwise (at a dropping rate of 0.08 mL / s) into the metal salt solution for contact reaction to obtain intermediate I;

[0067] (2) transferring the intermediate I to a Teflon-lined stainless steel autoclave for hydrothermal reaction, naturally cooling the product after the hydrothermal reaction to room temperature, collecting the precipitate by centrifugation and drying it in a vacuum drying oven to obtain a precursor;

[0068] The drying temperature was 50°C and the time was 8h;

[0069] (3) Grinding the precursor into powder (the average particle size is the same as that of Example 1), and calcining the powdered precursor in an air atmosphere to obtain a catalyst named DJ1.

[0070] Comparative Example 2

[0071] This comparative example was carried out in a similar manner to Example 1, except for the formulation, as shown in Table 1, to prepare a directional anchored catalyst named DJ2.

[0072] Comparative Example 3

[0073] This example is carried out by a method similar to that of the example, except that the dripping rate of ammonia monohydrate is 0.20 mL / s in this example. The rest is the same as that of example 1, and a directional anchored catalyst is prepared, named DJ3.

[0074] Table 1

[0075] Example 1 Example 2 Example 3 Comparative Example 2 <![CDATA[Fe(NO 3 ) 3 9H 2 O dosage / mmol]]> 4.0 3.5 3.0 4.95 <![CDATA[Ni(NO 3 ) 3 6H 2 O dosage / mmol]]> 1.0 1.5 2.0 0.05 Deionized water / mL 60 Same as Example 1 Same as Example 1 Same as Example 1 Amount of ammonia monohydrate / mL 1.6 Same as Example 1 Same as Example 1 Same as Example 1 Hydrothermal reaction Temperature / ℃ 180 160 Same as Example 1 Same as Example 1 Time / h 12 14 Same as Example 1 Same as Example 1 Calcination treatment Same as Example 1 Same as Example 1 Temperature / ℃ 450 550 Same as Example 1 Same as Example 1 Time / h 6 3 Same as Example 1 Same as Example 1 Catalyst naming J1 J2 J3 DJ2

[0076] Test Example 1

[0077] (1) The morphology of the directional anchored catalyst prepared in Example 1 was tested using a scanning electron microscope. The results are as follows: Figure 1 As shown in:

[0078] pass Figure 1 It can be seen that the directional anchored catalyst prepared in Example 1 is a nanosheet with an average thickness of 150 nm, and the nanosheet is uniform and regular.

[0079] (2) The chemical composition of the directional anchoring catalyst prepared in Example 1 was analyzed by X-ray photoelectron spectroscopy (XPS) according to the method specified in GB / T 33502-2017. The results are as follows: Figure 2 As shown:

[0080] pass Figure 2It can be seen that the Fe element in the chemical composition of the directional anchoring catalyst prepared in Example 1 of the present invention exists in two valence states of +2 and +3, and is mainly in the +3 valence state, which indirectly reflects the fact that the +2 valent Fe is replaced by the +2 valent Ni.

[0081] (3) The crystal structures of the catalysts J1-J3, DJ1 and DJ2 prepared in the above examples were tested by XRD diffractometer according to the method specified in GB / T5225-1985. The results are as follows: Figure 3 As shown:

[0082] pass Figure 3 It can be seen that the directional anchoring catalyst Ni prepared in Examples 1 to 3 of the present invention is NiFe 2 O 4 The structural form of α-Fe 2 O 3 (110) crystal plane.

[0083] (4) The compositions of the catalysts prepared in the above examples were tested according to the method specified in GBT3284-2015. The results are shown in Table 2.

[0084] Table 2

[0085] Catalyst composition <![CDATA[The molar ratio of the content of Fe 2 O 3 and Ni a Fe 2-a O 3 in the catalyst]]> Example 1 <![CDATA[Fe 2 O 3 Japanese 0.4 Fe 1.6 O 3 ]]> 1:0.29 Example 2 <![CDATA[Fe 2 O 3 Japanese 0.6 Fe 1.4 O 3 ]]> 1:0.24 Example 3 <![CDATA[Fe 2 O 3 Japanese 0.8 Fe 1.2 O 3 ]]> 1:0.30 Comparative Example 1 <![CDATA[Fe 2 THE 3 ]]> / Comparative Example 2 <![CDATA[Fe 2 O 3 Japanese 0.02 Fe 1.98 O 3 ]]> 1:0.11 Comparative Example 3 <![CDATA[Fe 2 O 3 Japanese 0.3 Fe 1.7 O 3 ]]> <![CDATA[Fe 2 O 3 and Ni 0.3 Fe 1.7 O 3 The molar ratio of the content is 1:0.22]]>

[0086] Test Example 2

[0087] The catalytic soot oxidation performance of each catalyst prepared in the above examples was tested respectively. The reaction device was assembled from a micro fixed bed reactor, a micro reaction stand (self-made), a flow control system, a temperature control system, a heating furnace, a fixed bed reactor and a gas chromatograph (GC-9890B). The specific test steps are as follows:

[0088] a. Weigh 100 mg of each of the above catalysts, mix them with 10 mg of soot particles respectively, and make them in loose contact to obtain a mixture;

[0089] b. The above mixtures were respectively loaded into a quartz tube reactor and 5 vol.% O 2 , 0.01 vol. % NO and Ar, total flow rate 50 mL min -1 ; The heating rate is 2℃ / min, from 25℃ to 550℃;

[0090] The sampling interval was 4 minutes, and CO and CO were recorded on the chromatographic workstation. 2 content, CO and CO produced by soot oxidation 2 Content integral, CO and CO 2The temperatures corresponding to the sum of the integral areas when the soot conversion rate is 10%, 50%, and 90% are denoted as T 10 , T 50 and T 90 , corresponding to the ignition temperature, the temperature at which the conversion rate is 50%, and the temperature at which the conversion rate is 90%;

[0091] CO 2 Selectivity = CO 2 Content / (CO content+CO 2 Content), where the detection port CO 2 The maximum selectivity is recorded as S CO2 m The specific results are shown in Table 3.

[0092] Table 3

[0093]

[0094] Test Example 3

[0095] The present invention illustratively tests the stability of the catalyst J1 prepared in the above Example 1, and the specific test steps are as follows:

[0096] S1, weighing 100 mg of J1 catalyst and mixing it with 10 mg of soot particles, loosely contacting them, to obtain a mixture I;

[0097] S2. The mixture I was placed in a quartz tube reactor, and 5 vol.% O2, 0.1 vol.% NO and Ar were introduced at a total flow rate of 50 mL min -1 The heating rate was 2°C / min, from 25°C to 550°C, and the sampling interval was 4min. After one cycle was completed, the catalyst samples in the quartz tube reactor were collected.

[0098] S3, the catalyst sample collected in the quartz tube reactor is fully mixed with the soot particles at a mass ratio of 10:1 again, and the mixture is in loose contact. The remaining steps are the same as S2, and the second cycle is completed to collect the catalyst sample in the quartz tube reactor.

[0099] S4. Complete five cycles according to step S3 and record CO and CO on the chromatographic workstation. 2 Content. CO and CO produced by soot oxidation 2 The content was integrated and the T values ​​of 5 cycles were recorded. 10 , T 50 and T 90 , and SCO 2 m , test results see Figure 4 .

[0100] pass Figure 4It can be seen that the T10, T50 and T90 of the directional anchoring catalyst prepared in Example 1 of the present invention remain basically unchanged after five cycles, and the SCO 2 m It is close to 100%, indicating that the catalyst has excellent catalytic stability.

[0101] It can be seen from the above results that the directional anchored catalyst provided by the present invention has excellent stability and catalytic activity, is suitable for catalytic reactions that require high-temperature treatment, especially in the field of eliminating carbon soot particles in motor vehicles, and can effectively reduce the emission of carbon soot particles.

[0102] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A directional anchored catalyst, characterized in that: The catalyst contains α-Fe2O3 and Ni a Fe 2-a O3; where 0.3<a≤0.8; The catalyst is a nanosheet with an average thickness of 100-150 nm, and the Ni in the catalyst a Fe 2-a O3 is anchored on the (110) crystal plane of the α-Fe2O3.

2. The catalyst according to claim 1, characterized in that The α-Fe2O3 and Ni a Fe 2-a The molar ratio of O3 content is 1:0.1-0.

3.

3. The catalyst according to claim 1 or 2, characterized in that 0.4≤a≤0.6。 4. A method for preparing a directional anchored catalyst, characterized in that: The method includes: (1) adding ammonia monohydrate dropwise to a metal salt solution to carry out a contact reaction to obtain an intermediate I; (2) subjecting the intermediate I to a hydrothermal reaction to obtain a precursor; (3) calcining the precursor in an air atmosphere to obtain a directional anchored catalyst; The metal salt solution contains Fe in a molar ratio of 1.5-4:

1. 3+ and Ni 2+ ; Calculated on the basis of metal ions, the dropping rate of the ammonia monohydrate is 0.04-0.10 mL / s for every 1 mmol of the metal salt solution.

5. The method according to claim 4, characterized in that In step (1), the amount of ammonia monohydrate used is 0.3-0.4 mL per 1 mmoL of the metal salt solution.

6. The method according to claim 4 or 5, characterized in that: The metal salt solution contains Ni 2+ and Fe 3+ of nitrate solution.

7. The method according to any one of claims 4 to 6, characterized in that: In step (2), the conditions of the hydrothermal reaction include: temperature of 150-180° C. and time of 10-14 h.

8. The method according to any one of claims 4 to 7, characterized in that: In step (3), the calcination treatment conditions include: temperature of 450-550°C and time of 3-6h.

9. The directional anchored catalyst prepared by the method according to any one of claims 4 to 8.

10. Use of the directional anchored catalyst according to claim 1 or 9 in the elimination reaction of soot particles in motor vehicle exhaust.